Job Vacancy Index for Costa Rica 2010 - 2021 - Sánchez Gómez, Manuel Esteban (2023)
This paper presents a first labor demand index for Costa Rica, calculated from the National Employment Agency (NEA) website. The index shows procyclical behavior. Furthermore, the vacancy creation index showed a trend consistent with the heterogeneity in the economic activity across sectors, regions, and occupations during 2010-2021. Particularly, in the context of the COVID-19 pandemic, the activities most affected by the mobility restrictions during the first half of 2020 also reported the deepest contractions in their labor demand. Between the second half of 2020 through the last months of 2021, industries such as manufacturing, administrative and support service activities, information, and communication stood out for their more pronounced increase in their labor demand. Firms located in Heredia, Cartago, and Guanacaste, and occupations related to operators and assemblers of manufactures, professionals and scientists, and workers for support services and administrative services also reported higher vacancy creation.